2002
DOI: 10.1063/1.1513796
|View full text |Cite
|
Sign up to set email alerts
|

Scaling parameters for underexpanded supersonic jets

Abstract: An analysis and experiments were carried out to study the spreading and centerline property decay rates of underexpanded supersonic jets. The main purpose was to determine a suitable set of normalization parameters that would account for the initial expansion process and allow for a comparison of the asymptotic mixing rates of jets within a large range of exit-to-ambient pressure ratios. A set of expressions were developed for after-expansion equivalent jet exit diameter, velocity, temperature, and density to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 11 publications
2
53
0
Order By: Relevance
“…16, we have k ∼ π /D for NPR = 4.5 and k ∼ 2π /D otherwise. The antisymmetry shown earlier for mode pair (1,2) gives an azimuthal wavenumber |m| = 1 and characterizes the helical mode. Gutmark et al 49 reported that the dominant mode in a similar configuration satisfied |m| = 1, supporting the present finding.…”
Section: G Proper Orthogonal Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…16, we have k ∼ π /D for NPR = 4.5 and k ∼ 2π /D otherwise. The antisymmetry shown earlier for mode pair (1,2) gives an azimuthal wavenumber |m| = 1 and characterizes the helical mode. Gutmark et al 49 reported that the dominant mode in a similar configuration satisfied |m| = 1, supporting the present finding.…”
Section: G Proper Orthogonal Decompositionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Such high speed jets can also be observed in geophysical applications, for example, volcano eruptions release large amounts of gas in the atmosphere featuring weak shocks, compression waves and Machdisks. 8 Other examples are jet formation during accidental release of pressurized hydrogen through a small hole or a crack.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of leak scenarios will occur from a pressurized source creating an under-expanded jet. Notional nozzle models allow the replacement of the compressible aspect of the jet with atmospheric equivalent boundary conditions (Birch et al 1984(Birch et al , 1987Ewan and Moodie 1986;Harstad and Bellan 2006;Yuceil and Otugen 2002), after which the jet is regarded as atmospheric and modeled thusly. A recent study concluded that the downstream aspect of an underexpanded jet conforms to the current self-similarity assessment (Ruggles and Ekoto 2012).…”
Section: Introductionmentioning
confidence: 99%
“…(Note in Figure 5 that the CFD solution has a recirculation region attached to the outer shroud that slows the flow at this location.) In the downstream portion of the jet, a velocity profile 12 approximating a Gaussian distribution, should be reached as shown by the CFD calculation, but an approximate "top hat" profile is shown by the instantaneous measured data instead (Fig. 9(b)).…”
Section: B Streamwise Velocity Profiles Near Thementioning
confidence: 99%